Expression Analysis of Genes Related to Auxin Metabolism at Different Growth Stages of Pak Choi - Yuxiang Hou; Xueting Wang; Zhujun Zhu; Mengxia Sun; Meilan Li; Leiping Hou (Horticultural Plant Journal, 2020)
Pak choi is a low-temperature vernalized plant that readily undergoes premature bolting during spring, but little is known about the governing molecular regulation of vernalization. In order to enhance our understanding of mechanism about premature bolting, we discussed the relationship between auxin (indole-3-acetic acid, IAA) and flowering of pak choi. During vernalization, hormone metabolism is an important regulatory pathway, and IAA plays a specific role. IAA metabolism has been studied in Arabidopsis thaliana and other plants, but not in pak choi. In this paper, the IAA content in pak choi shoot apices during vernalization and different growth stages was compared. The IAA content decreased significantly after low-temperature treatment (4 °C) and then increased rapidly during vegetative growth. During floral bud initiation, the IAA content decreased rapidly and was the lowest. Expressions of genes encoding key IAA metabolic enzymes were analyzed, and a major synthetase-encoding gene was downregulated, while a key degrading enzyme-encoding gene was upregulated during each comparison period, resulting in decreased IAA content. Expressions of four genes (Bra034975, Bra030246, Bra012239 and Bra040296) were consistent with changes in the IAA content. The functions of differentially expressed genes (DEGs) were analyzed, and 15 DEGs were found to be related to IAA metabolism. The findings illuminated the molecular mechanism regulating IAA content during vernalization in pak choi. Keywords: Pak choi, Brassica rapa, Vernalization, Auxins, Gene expression, Hormone metabolism